Analisis Indeks Potensi Lahan Pertanian Padi Sawah Menggunakan Sistem Informasi Geografis Di Kabupaten Bandung - Silalahi, Rebecca Cristia; Ilham B. Mataburu; Kusumawati, Lia (JPIG (Jurnal Pendidikan dan Ilmu Geografi), 2025)
Currently, one of the main problems in the agricultural industry is the conversion of irrigated rice fields. The potential for irrigated rice fields in Bandung Regency is needed to help overcome agricultural problems. This study aims to find out how to analyze the potential index of irrigated rice fields and land that is not rice fields but in Bandung Regency by mapping the potential index of rice fields using the Geographic Information System. The GIS analysis used was using scoring and overlay on the parameters used. The results of the overlay of each parameter produced an index of irrigated rice field potential which showed that rice fields in Bandung Regency were most planted on land that had IPL with a medium class, which was 697.99 Km² with a percentage of 39%. Land that is not a rice field and has the potential to become a new rice field is 5 classes, namely very high with an area of 42.34 Km2 consisting of 12 sub-districts, land with a high category has an area of 321.44 Km² consisting of 14 sub-district areas, in the medium potential class, which is the most dominating Bandung Regency, which is 633.79 Km2 which covers 20 sub- district areas, the distribution of low-class potential land covers 24 sub-districts covering an area of 355.36 Km2, while in the very low land potential class spread across 20 sub-districts covering an area of 98.21 Km2. As a recommendation, rice fields with high potential should be maintained as rice fields, and rice fields with low potential should be processed more optimally.